LEONAS PANAVAS’S BOOKBINDINGS FROM THE POINT OF VIEW OF APPLIED AND ARTISTIC BOOKBINDING - Taukinaitytė-Narbutienė, Rūta (Knygotyra, 2017)
The aim of the paper is to discuss works of the little-known and little-researched bookbinder Leonas Panavas (1942‒2011), to identify the key features of his work, the influence of his bibliophilic interests and of his profession as a metalworker, and to attempt an outline of his significance and place in the culture of the Lithuanian book. Although L. Panavas was an autodidact, it is important to record his legacy because bookbinders like him were extremely rare. He bound hundreds of books. Thus his work, in one way or another, constitutes part of the heritage of manual bookbinding of the twentieth century, characterizes its peculiarities, and continues the tradition. L. Panavas employed a number of main binding methods: he did not sew headbands but paid much attention to the decoration (dyeing) of the block edge. He tried out the technique of paper marbling. He also restored old worn books and possessed numerous self-made tools and even a hot press. Some works are not of high technical quality due to the lack of geometrical symmetry and order, as well as poor or low-quality materials used. However, his late works show that with passing years this master refined his craft considerably. He decorated books mostly by blind stamping and gilt stamping (using gold imitation) with clichés. Since he was a metal turner, he had the opportunity to make his own clichés and relief metal plates for stamping. He would find other clichés in printing shops, arts and crafts production centres, and flea markets. By selecting and matching several individual motifs and ornaments he formed various compositions. He approached book titles in a similar way, by assembling words from separate letters. Art as self-expression is not the main purpose of his works: it was just a supplementary means of book decoration. Indeed, the covers of the books he bound are decorated, yet it is not his original design. This master neither created nor drew the motifs he used but employed existing motifs and reiterated the styles of the past. With regard to the principles of artistic construction and characteristic features, these covers hardly differ from similar works of the Kaunas masters representing the interwar period, or even nineteenth-century historicism bindings – from the point of view of form they are timeless. Cover compositions are often eclectic, the image is overloaded, the elements and anachronisms are stylistically incompatible. Despite that he managed quite well to maintain the compositional equilibrium His blind stamping and gilt stamping were balanced, and he was in control of the typographical means of expression. L. Panavas paid much attention to typefaces. This apt and intuitive feeling for typefaces came from his experience as a book lover. Among the notes of L.eonas Panavas, a sketch by the prominent painter, collector and bibliophile Kazys Varnelis, which manifestly showed the painter’s characteristic minimalist style, was found. L. Panavas followed this sketch to bind a book for K. Varnelis. The ornamental stamping, characteristic of L. Panavas’s books, does not decorate other bindings done for K. Varnelis. It shows how important the customers with their aesthetic requirements and taste are to artistic bookbinding. Using the resources available in the book-related environment of his time, L. Panavas accumulated an iconographic collection of local book decoration, which accommodated styles from the nineteenth century to present time. In this way his works continue and establish the qualities of Lithuanian bookbinding.